Façonner la prescription, influencer les médecins - Jérôme Greffion; Thomas Breda (Revue de la Régulation)
In order to restrain the regulation by the public authorities of its activities, the pharmaceutical industry leaves in the shadows, as much as possible, the extent of its promotional effort. Yet, we show that drug promotion is one of its core businesses. The related expenses are tremendous. They represent at least 20 % of the turnover of this sector and drug detailing request up to 40 % of the total staff of the large pharmaceutical companies, which have become marketing giants. But how can we reconcile this analysis on one hand and the fact that many physicians deny the influence of drug promotion on their practice and the results of econometric studies underlining the weak effect of drug detailing on the other hand? Do the large pharmaceutical firms shape the demand on their markets, according to the model of the revised sequence, or do they suffer from a rationality problem, massively investing into a low profitable activity? As an alternative to microeconomic studies of witch we discuss the results in the light of our ethnographic study, we intend to use a macroeconomic approach to deal with this question. Our results plead for a strong link between the intensity of the word of drug representatives and physicians’ prescriptions, which takes the form of an incentive to prescribe more expansive and newer drugs.